Ion bridging enables high-voltage polyether electrolytes for quasi-solid-state batteries - Tianyi Hou; Donghai Wang; Bowen Jiang; Yi Liu; Jia Kong; Yanbing He; Yunhui Huang; Henghui Xu (Nature Communications)
Abstract Polyether electrolytes have been widely recognized for their favorable compatibility with lithium-metal, yet they are hampered by intrinsically low oxidation thresholds, limiting their potential for realizing high-energy Li-metal batteries. Here, we report a general approach involving the bridge joints between non-lithium metal ions and ethereal oxygen, which significantly enhances the oxidation stability of various polyether electrolyte systems. To demonstrate the feasibility of the ion-bridging strategy, a Zn2+ ion-bridged polyether electrolyte (Zn-IBPE) with an extending electrochemical stability window of over 5 V is prepared, which enables good cyclability in 4.5 V Li||LiCoO2 batteries. Ampere-hour-level quasi-solid-state batteries of SiO-graphite||LiNi0.8Mn0.1Co0.1O2 (10 Ah, N/P ratio of 1.12, 303 Wh kg−1 at 0.1 C based on the total weight of the pouch cells) and 60 μm-Li||LiNi0.9Mn0.05Co0.05O2 (18 Ah, N/P ratio of 2.5, 452 Wh kg−1 at 0.33 C based on the total weight of the pouch cells) pouch cells with Zn-IBPE present elevated electrochemical performance, benefiting from adequate interfacial stability. Nail penetration tests evidence high battery safety enabled by Zn-IBPE in 4 Ah graphite||LiNi0.8Mn0.1Co0.1O2 pouch cells without combustion or smoke. This work offers a pathway for designing high-voltage polymer electrolytes and a general solution for achieving high-performance quasi-solid-state batteries.